An unexpected finding of a rare intrascrotal lesion: the sertoliform cystadenoma of the rete testis. (20th February 2013) - Sahnan, Kapil; Manjunath, Aditya; Vaughan-Shaw, Peter G; Mitsopoulos, Grigorios
Abstract : A 19-year-old man presented with a right testicular swelling. Testicular ultrasound demonstrated areas suspicious for malignancy and so it was decided to proceed for a right radical inguinal orchiectomy. Initial histological examination revealed a multiloculated cystic lesion at the area of the rete testis yet normal testicular parenchyma elsewhere. Specialist histological opinion was sought from the regional teratoma multi-disciplinary team which confirmed the diagnosis of a sertoliform cystadenoma, an extremely rare benign testicular neoplasm. The recognition of the benign nature of the mass enabled complete reassurance to be offered to the patient and avoided further oncological treatment.